2018
DOI: 10.12669/pjms.345.14569
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-loaded bone cement spacer usage combined with membrane induction in infected gap non-unions: A case series

Abstract: Objective:To explore the clinical effects upon gap nonunion of antibiotic-loaded bone cement spacer combined with membrane induction on infected bone defects.Methods:The data of 16 patients with infected bone defects admitted in General Hospital of Shenyang Military Area Command from January 2009 to January 2011 were analyzed retrospectively. There were 12 males and 4 females aged between 24-63 years age (average 43.1 ± 9.7) who had received antibiotic laiden bone cement spacer treatment. Stage-1, debridement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Moreover, bone cement can provide local support and facilitate early functional exercise [ 28 ], although there is no standard for the use of antibiotics in bone cement, because excessive addition will reduce the mechanical strength. But a study found that adding 8 grams of antibiotics to 40 grams of bone cement is still safe [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bone cement can provide local support and facilitate early functional exercise [ 28 ], although there is no standard for the use of antibiotics in bone cement, because excessive addition will reduce the mechanical strength. But a study found that adding 8 grams of antibiotics to 40 grams of bone cement is still safe [ 29 ].…”
Section: Discussionmentioning
confidence: 99%